Americanization in Two Immigrant Theravada Buddhist Temples. Paul David Numrich. - Bell, Sandra (Buddhist Studies Review, 1996)
Americanization in Two Immigrant Theravada Buddhist Temples. Paul David Numrich. University of Tennessee, Knoxville 1996. xxiv, 181 pp. Illustrations. $25. ISBN 0-87049-905-X.